2018
DOI: 10.1016/j.amc.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of degenerate stochastic Kawarada equations via a semi-discretized approach

Abstract: The numerical solution of a highly nonlinear two-dimensional degenerate stochastic Kawarada equation is investigated. A semi-discretized approximation in space is comprised on arbitrary nonuniform grids. Exponential splitting strategies are then applied to advance solutions of the semi-discretized scheme over adaptive grids in time. It is shown that key quenching solution features including the positivity and monotonicity are well preserved under modest restrictions. The numerical stability of the underlying s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Our ongoing research has been including effective schemes on variable spacial and temporal meshes for different financial products and simulations. We have also been considering effective adaptation strategies such as those investigated in [16,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our ongoing research has been including effective schemes on variable spacial and temporal meshes for different financial products and simulations. We have also been considering effective adaptation strategies such as those investigated in [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some key parameters used are shown in Table 1. Further, a Crank-Nicolson type temporal integrator will be utilized for advancing our semi-discretized system (2.9), (2.12), with ∆τ as the temporal step [18]. It has been known that λ = ∆τ/c 2 , where c = min {h, k} , play an effective role of the Courant number [14,16].…”
Section: Computational Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical studies regarding the integer order Kawarada equations have often considered the solution positivity and monotonicy [15,17,16,8]. These properties are critical in many situations modeled by these equations, such as solid-fuel combustion [3].…”
Section: Solution Positivity and Monotonicitymentioning
confidence: 99%
“…In particular, operator splitting methods have been shown to be effective and efficient numerical methods, as they may often be constructed to preserve stability while being explicit with desirable convergence rates [9,10,19,20,23,24]. While splitting methods have primarily been studied in the deterministic setting, there have been several recent studies regarding their efficacy in application to stochastic problems [2,17,18,21]. In particular, it has been shown that the splitting of deterministic and stochastic counterparts of differential equations can prove effective by increasing convergence rates without the inclusion of derivative terms [2,5,17].…”
Section: Introductionmentioning
confidence: 99%